The Role of the Immune Response in Brain Metastases: Novel Imaging Biomarkers for Immunotherapy - Zakaria, Rasheed; Radon, Mark; Mills, Samantha; Mitchell, Drew; Palmieri, Carlo; Chung, Caroline; Jenkinson, Michael D. (Frontiers in Oncology, 2021)
Brain metastases are a major clinical problem and immunotherapy offers a novel treatment paradigm with the potential to synergize with existing focal therapies like surgery and radiosurgery or even replace them in future. The brain is a unique microenvironment structurally and immunologically. The immune response is likely to be crucial to the adaptation of systemic immune modulating agents against this disease. Imaging is frequently employed in the clinical diagnosis and management of brain metastasis, so it is logical that brain imaging techniques are investigated as a source of biomarkers of the immune response in these tumors. Current imaging techniques in clinical use include structural MRI (post contrast T1W sequences, T2 and FLAIR), physiological sequences (perfusion and diffusion weighted imaging) and molecular imaging (MR spectroscopy and PET). These are reviewed for their application to predicting and measuring the response to immunotherapy in brain metastases.